Prevalence of musculoskeletal symptoms among production line workers in a printing manufacturing company, Malaysia - Foong, M. C.; Adon, Mohd Yusoff; Baharudin, Mohd Rafee; Ariffin, Ahmad Azuhairi (Community Health Society Malaysia, 2014)
Background: Leading cause of occupational injury in the developed and developing countries relates to musculoskeletal disorders (MSDs) and also is a main cause of work- related disability and lost-time illnesses. The objectives of this study are to determine the prevalence of self-reported musculoskeletal symptoms among printing production line workers and to examine the relationship between musculoskeletal symptom and individual risk factors. Material and Method: A cross-sectional study was carried out in a commercial printing company in Klang Valley, Malaysia. Respondents were randomly selected based on the inclusive criteria and a total of 250 printing production line workers were involved in the study. An Interview section of each respondent was conducted to obtain the information and musculoskeletal symptoms through validated Malay version of Standardized Nordic Questionnaire (SNQ). Result: The response rate was 85.9%. The prevalence of musculoskeletal symptoms was 79.6%. The most common musculoskeletal symptoms were from the lower back (48.0%), shoulders (44.4%), knees (32.8%), and neck (29.6%). Respondents to be a male, heavy body weight, and high body mass index (BMI) had significantly associated with musculoskeletal symptoms on lower back (p<0.05). There were significant association between heavy body weight and long duration of employment with musculoskeletal symptoms on knees (p<0.05). Conclusion: The prevalence of musculoskeletal symptoms among the printing production line workers was high and it was related to a person’s individual factors. Gender, weight, BMI, and duration of employment were implied increase risk of musculoskeletal disorder (MSD).